AKTIVITAS ANTIBAKTERI MINYAK ATSIRI SEREH WANGI (Cymbopogon citratus) TERHADAP BAKTERI Escherichia coli, Propionibacterium acne, Staphylococcus aureus - Hermawati, Ema; Tanfil T, Ardy; Bayu Chandra, Pra Panca (Jurnal Farmasi (Journal of Pharmacy), 2023)
Citronella oil (Cymbopogon citratus) is an essential oil that has potential as an antibacterial. The main compounds of citronella oil are citronellal, geraniol and citronellol. The purpose of this study was to determine the bacterial inhibitory activity of citronella essential oil against Escherichia coli, Propionibactaerium acne, Staphylococcus aureusbacteria. The research method used was an experimental laboratory using a basic research design completely randomized design (CRD) with a factorial pattern of 24 hours incubation time at 37oC and different concentrations of citronella oil (Cymbopogon citratus) (10%, 20% and 30%) compared to comparator, namely tetracycline. The antibacterial test used the disc diffusion method. The results of the antibacterial activity test of citronella essential oil (Cymbopogon citratus) showed results as a strong category, namely having an inhibition zone ranging from 10-20 mm. The optimum concentration to inhibit the bacteria Escherichia coli, Propionibacterium acne, Staphylococcus aureus is at a concentration of 30%.